If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -3) = 2x + 4 Reorder the terms: 2(-3 + y) = 2x + 4 (-3 * 2 + y * 2) = 2x + 4 (-6 + 2y) = 2x + 4 Reorder the terms: -6 + 2y = 4 + 2x Solving -6 + 2y = 4 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2y = 4 + 6 + 2x Combine like terms: -6 + 6 = 0 0 + 2y = 4 + 6 + 2x 2y = 4 + 6 + 2x Combine like terms: 4 + 6 = 10 2y = 10 + 2x Divide each side by '2'. y = 5 + x Simplifying y = 5 + x
| b-5=1 | | f(-9)=x^2+4x | | xy+4x-3y-12=0 | | w-19w= | | 2(x+6)=4x-10 | | 3x-5=-4x+30 | | -5x-2=x-20 | | 2y^2-y-28=0 | | -5x+5=2x+26 | | 13a-8=13 | | 4x-4=-x+6 | | 2x^3+5x^2-63x=0 | | 6x-8=5+6x-4 | | -3x+4=-3x-3 | | -0.08x+0.1(x+4800)=492 | | -3x-4=-5x+4 | | 4x-3=4x-4 | | 13(-11)=-11(13) | | 2-10x=-8 | | 0=2x^2+18x+28 | | -x-1=5x-21 | | 60=x+(x+10) | | 5x(3+7)= | | 3=1.2+x | | 9x+1+x+9=5(2x+2) | | 4n+12=5n-3n+2 | | 17.50+175.00+234.00=1196.50 | | 2+5(x-1)=47 | | 2x+1=-x-14 | | -2x+1=-3x-1 | | 8-6x-2=x+9 | | 8-5x=3x+14 |